Mikrokredittens globale fortælling og dens etiske problemstillinger - Jensen, Thessa (Academic Quarter | Akademisk kvarter, 2011)
The global narrative of microloan and its ethical issues by Thessa Jensenhighlights microcredit’s chronological development from its origins in Bangladesh to its potentials today in the era of an Internet-based economy. In this narrative there is a conflict between the poor borrowers (the original recipients) and the development of microcredit institutions that will only work with market economy logics: profitability and growth. Jensen analyzes the ethical challenges that this conflict provides and tries to find an answer to them involving the ideas of Løgstrup and Levinas.